Development Economics and Re-construction of Developing Countries: Reflections and Insights - Bharti, Simant Shankar (Social Development and Security, 2020)
Development economics emerged as a new theoretical approach that focuses on the re-construction of developing countries as the study focus on improving fiscal, economic and social conditioning. Development economics also do an analysis of developing countries from critical assessment, which contributes to the making of development policy. This paper tries to explore the understanding of theoretical approaches to development economics and a helping strategy or re-construction instrument for developing countries. Through the reflections, the article critically argued the contribution of development economics in making development policy for developing countries. It is also focused on those development policies by international institutions and governments, how this is opportunities and state-building instrument. But recent global pandemic such COVID-19 raises a critical question for both donor and recipient of aid. Moreover, there is required a reality check to the re-construction of developing countries.